The therapeutic potential of microRNAs to ameliorate spinal cord injury by regulating oligodendrocyte progenitor cells and remyelination - Qiu, Shanru; Dai, Hui; Wang, Yu; Lv, Yehua; Yu, Bin; Yao, Chun (Frontiers in Cellular Neuroscience, 2024)
Spinal cord injury (SCI) can cause loss of sensory and motor function below the level of injury, posing a serious threat to human health and quality of life. One significant characteristic feature of pathological changes following injury in the nervous system is demyelination, which partially contributes to the long-term deficits in neural function after injury. The remyelination in the central nervous system (CNS) is mainly mediated by oligodendrocyte progenitor cells (OPCs). Numerous complex intracellular signaling and transcriptional factors regulate the differentiation process from OPCs to mature oligodendrocytes (OLs) and myelination. Studies have shown the importance of microRNA (miRNA) in regulating OPC functions. In this review, we focus on the demyelination and remyelination after SCI, and summarize the progress of miRNAs on OPC functions and remyelination, which might provide a potential therapeutic target for SCI treatments.